Analisis Impor Beras Indonesia dari Negara Asia Tahun 2025 - Azizah Nur Fauziah Rahmah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
from Asian countries in 2025. The research employed a descriptive method with a simple quantitative approach using secondary data from Statistics Indonesia (BPS) up to 2024 and supporting publications in 2025. The findings show that Indonesia imported 4.52 million tons of rice in 2024, mainly from Thailand, Vietnam, Pakistan, and Myanmar. In 2025, rice imports declined significantly to approximately 450 thousand tons due to increased domestic production, government import control policies, and changing global market conditions. This decline creates opportunities to strengthen national food security and reduce dependence on imported rice. However, challenges remain, including climate uncertainty, global price fluctuations, and the need to maintain a balance between domestic production and price stability. Therefore, sustainable and appropriate policies are essential to support Indonesia's agricultural trade, particularly in the rice sector.